Parametric and Robust Optimization of a Vibration Absorber with a Generalized Cubic, Quadratic and Non Integer Nonlinearities of Damping and Stiffness - Bouazizi, M.–Lamjed; Ghanmi, S.; Nasri, R. (IntechOpen, 2011)
None